Evaluation of a Nurse Practitioner Led Procedural Support Service for Children With Procedural Anxiety: An Effectiveness–Implementation Study. - Plummer, Karin; Kotzur, Catherine; Williams, Suzanne; Vongkiatkajorn, Krittika; Lee‐Archer, Paul; Doyle, Rebecca; Keyser, Janelle; Wighton, Amber; Keogh, Samantha (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2026)
Aim: To evaluate the clinical effectiveness of a Nurse Practitioner led procedural support service for children with procedural anxiety, and identify facilitators and barriers to its sustained implementation and optimisation. Design: An effectiveness–implementation hybrid type 3 study used a prospective mixed methods evaluation approach. Methods: From December 2022 to May 2023, data were collected from children, parents and clinicians using a nurse practitioner‐led service at a quaternary paediatric hospital in Brisbane, Australia. A prospective audit assessed clinical outcomes, while qualitative interviews explored implementation barriers and facilitators. Findings: The clinical audit (n = 40) confirmed the service was effective and safe, ensuring procedural completion with minimal distress. Descriptive statistics indicated low pain and anxiety scores. There was a moderate negative relationship between pain scores and the use of distraction techniques. Interviews with thirty‐three participants showed the service improved access to procedural care, reduced the need for physical restraint and general anaesthesia, and enhanced clinical workflow through preadmission assessments. Conclusion: Utilising a Nurse Practitioner support service represents a safe and effective strategy to enhance access for paediatric patients with procedural anxiety. Implications for the Profession and Patient Care: This study underscores the significance of specialised nursing roles in managing paediatric procedural anxiety, offering a replicable model to enhance procedural outcomes and mitigate medical trauma across healthcare settings. Impact: Minimising pain and distress is important in all clinical encounters with children to reduce the risk of medical‐related trauma and the future avoidance of healthcare. Reporting Method: The report of study outcomes was guided by the Standards for Reporting Implementation Studies (StaRI) initiative. Patient or Public Contribution: Patients or the public were not included in the design, conduct or reporting of the study. What Does This Paper Contribute to the Wider Global Clinical Community?: This study demonstrates the value of applying an implementation science framework to examine the implementation and optimisation of an advanced practice nursing role.The delivery of procedural sedation is historically managed by medical personnel. The use of a Nurse Practitioner model is a safe alternative to both respond to the needs of patients with procedural anxiety, and reduce the unnecessary use of general anaesthesia.Investing in advanced practice nursing roles is valuable for supporting children with procedural anxiety and medical complexity.